Cutaneous allergic reaction due to alprazolam in a child - Meryem Ozlem Kutuk; Gulen Guler; Ulas Guvenc; Fevziye Toros; Tamer irfan Kaya (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2016)
Cutaneous allergic reactions due to drug intake may be triggered by many types of drugs such as atropine, anticonvulsants and benzodiazepines. But allergic reactions due to benzodiazepines are extremely rare. Alprazolam is a benzodiazepine which may be useful for refractory idiopathic urticaria due to antihistaminergic effect. Although antihistaminergic effect of alprazolam, a cold urticaria case and an angioedema case induced by alprazolam are known in the literature. In the case, we present a child suffering from cutaneous allergic reaction due to alprazolam at the first dose taken. [Cukurova Med J 2016; 41(2.000): 400-402]